PTU-129 The Role Of Primary Resection And Hepatic Resection In The Management Of Metastatic Pancreatic Neuroendocrine Tumours With Irresectable Liver Metastases. (9th June 2014) - Mills, L; Srirajaskanthan, R; Ramage, J; Prachalias, A; Srinivasan, P; Menon, K; Quaglia, A; Heaton, N
Abstract : Introduction: More than 40% of pancreatic neuroendocrine tumour (PNET) patients have liver metastases (LM) at diagnosis. Whilst it is agreed that, where possible, curative surgery offers the best outcomes, the role of debulking surgery in the context of irresectable LM remains unclear. There is also no clear evidence to support resection of the pancreatic primary in the context of irresectable liver metastases. The aim of this study is to investigate the survival benefits of different surgical treatments of LM. Methods: The notes of 111 PNET patients who had visited King's since 2004 were reviewed. 53 had LM at diagnosis and were divided into 3 cohorts: No Resection (NR) n = 27, Pancreatic Resection (PR) n = 6 and Pancreatic and Liver Resection (PLR) n = 11. Median follow-up was 40.2 months. Results: Median survival for all patients with liver metastases was 61.1 months. Survival was significantly worse for patients with no resection; NR (23 months) vs. PR (98 months) p = 0.047, NR (23 months) vs. PLR (n/a) p = 0.008, but there was no significant difference between PR and PLR. Of the 11 PLR patients, 6 received debulking rather than curative resection. Univariate analysis showed no significant survival difference between dubulking and curative liver resection; however, multivariate analysis showed that resectability of liver metastases was not a significant prognostic variable. Conclusion: Resection of the primary significantly improves survival in the presence of irrespectable liver metastases. There may be a role for debulking surgery in patients with irresectable liver metastases, however, the data so far does not appear to suggest a survival benefit over primary resection alone; larger studies are needed. Disclosure of Interest: None Declared.